2003
DOI: 10.2134/jeq2003.1857
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Retention Mechanisms of a Water Treatment Residual

Abstract: Water treatment residuals (WTRs) are a by-product of municipal drinking water treatment plants and can have the capacity to adsorb tremendous amounts of P. Understanding the WTR phosphorus adsorption process is important for discerning the mechanism and tenacity of P retention. We studied P adsorbing mechanism(s) of an aluminum-based [Al2(SO4)3 x 14H2O] WTR from Englewood, CO. In a laboratory study, we shook mixtures of P-loaded WTR for 1 to 211 d followed by solution pH analysis, and solution Ca, Al, and P an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
107
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 40 publications
16
107
0
1
Order By: Relevance
“…It can be explained that the abundance of aluminium ions in the sludge facilitated P removal from wastewater through ligand exchange. This is in agreement with the suggestions of Ippolito et al (2003) which state that P retention by water treatment plant residual may be due to chemisorption, as P may be initially adsorbed as an outer sphere complex or found in the diffuse ion swarm near the individual sludge particles.…”
Section: Discussionsupporting
confidence: 92%
“…It can be explained that the abundance of aluminium ions in the sludge facilitated P removal from wastewater through ligand exchange. This is in agreement with the suggestions of Ippolito et al (2003) which state that P retention by water treatment plant residual may be due to chemisorption, as P may be initially adsorbed as an outer sphere complex or found in the diffuse ion swarm near the individual sludge particles.…”
Section: Discussionsupporting
confidence: 92%
“…Because of their amorphous nature, WTRs have a large surface area (up to 105 m 2 g À1 ) [4] and are highly reactive. They have the proven ability to adsorb tremendous quantities of P [5,6] and have been shown to adsorb other oxyanions such as As(V), As(III), and ClO À 4 [7,8]. Water treatment residuals may also adsorb selenium species although this phenomenon and the bonding mechanisms have yet to be documented.…”
Section: Introductionmentioning
confidence: 99%
“…Different masses of alum sludge ranging between 0.1g to 0.5 g and 100 ml of P suspension were hours [8,11], 48 hours [10], 6 days [12] and up to 80 days [4] with initial P concentration ranged from 5.0 to 3,500 mg P/L were reported in similar studies. Then the samples were removed from the shaker and filtered using a 0.45 Millipore membrane filter to separate the solids from the liquid.…”
Section: Batch Adsorption Testsmentioning
confidence: 77%
“…Other recent studies explore the phosphorus adsorption ability of DWTS (especially aluminium based DWTS) and its use in other applications [6][7][8][9][10]. Ippolito et al [11] reported a high phosphorus-binding capacity of approximately 12.5 g P/kg DWTS while Dayton and Basta [12] claimed a capacity ranging from 10.4 to 37.0 g P/kg DWTS by examining 18 DWTSs in the U.S.…”
Section: Introductionmentioning
confidence: 99%